Factors associated with stroke among patients with type 2 diabetes mellitus in China: a propensity score matched study - He, Chenlu; Wang, Wei; Chen, Qian; Shen, Ziyuan; Pan, Enchun; Sun, Zhongming; Lou, Peian; Zhang, Xunbao (Acta diabetologica, 2021)
Objective This study aimed to examine the prevalence of stroke and associated factors of stroke in patients with type 2 diabetes(T2DM) in China. Methods Participants were 18,013 T2DM patients recruited with stratified random cluster sampling method from December 2013 to January 2014 in China. Propensity score matching was used to eliminate confounding effects between groups and logistic regression analysis was used to examine factors associated with stroke among T2DM patients. Results Overall, the prevalence of stroke in the subjects with T2DM was 9.5%. After nearest neighbor matching, smoking (OR = 1.60, 95%CI: 1.26–2.03), hypertension (OR = 2.96, 95%CI: 2.55–3.43), dyslipidemia (OR = 2.00, 95%CI: 1.71–2.33), family history of stroke (OR = 2.02, 95%CI: 1.61–2.54), obesity (OR = 1.21, 95%CI: 1.01–1.45) and sleep duration < 6 h/day (OR = 1.44, 95%CI: 1.20–1.73) or > 8 h/day (OR = 1.22, 95%CI: 1.05–1.42) were positively associated with stroke, whereas drinking 1–3 days/week (OR = 0.64, 95%CI: 0.45–0.90) or daily (OR = 0.45, 95%CI: 0.33–0.60), effective exercise (OR = 0.65, 95%CI: 0.57–0.73) and underweight (OR = 0.30, 95%CI: 0.13–0.71) were negatively related to stroke. Besides, the risk of stroke increased substantially with accumulation of above seven modified risk factors. The odds ratio values of stroke in patients having ≥ 5 of the above seven risk factors was 14.39 (95% CI: 8.87–23.26). Conclusions The prevalence of stroke was high among T2DM in China. It is of great significance to strengthen comprehensive management of health-related behaviors including smoking cessation, moderate alcohol consumption, effective exercise, 6–8 h of sleep duration, keeping normal weight and the prevention of hypertension and dyslipidemia to have sustained beneficial effects on improvements of stroke risk factors.